On the economic growth of Poland’s macro-regions against the background of uncertain prospects for the European Union (Economic and Political Thought, 2017)
The research problem: determination of the impact of investment in 2007and 2014 on the level of GDP growth in particular macro-regions in Polandin the long term. The main issue raised in the article is to define the investmentprocesses at a macro as well as a micro level from the perspectiveof companies in six Polish macro-regions. Investment in selected Europeancountries, especially in Poland, in contrast to the United States, remainssignificantly below the pre-crisis level. The decrease in investment spreadout to all sectors of the market, among others: companies, public sector,and also households. The aim of the article is to examine the importance ofinvestment in 2007 and 2014 in individual macro-regions in Poland, especiallyat the level of investment in fixed assets identified by modern economy,i.e. machinery, equipment, means of transport, housing, other buildings andstructures, IT-telecommunications equipment and solutions or intellectualproperty. Uncertainty of the future characterizes Europe, especially in theface of the strong inflow of migrants, against which Europe does not knowhow to defend. The research hypothesis: the condition necessary for theincrease in the competitiveness of the Polish economy in macro-regions, aswell as throughout the European Union, is the need to increase the investmentwith particular focus on those sectors that have the highest added valueand economic viability, and may become international, which will be conduciveto the competitiveness of the economy. The research method: review ofstatistical data, offering hypotheses and an attempt to verify them with theuse of methods that are commonly used in science. Expected results: fastereconomic growth of Poland in comparison to European countries.